Urgensi Pengujian Formil di Indonesia : Pengujian Legitimasi dan Validitas - Faiz Rahman (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
The review of the constitutionality of norms is a control mechanism that is carried out on the law-making procedures (procedural review) and the substance of the norm (substantive review). This is a consequence of a constitutional state and the rule of law. Cases of procedural review have often occurred in Indonesia, but the understanding and regulation is still relatively inconsistent as on substantive review. One of the reasons why this condition occurred is due to the lack of regulation regarding the procedure for the law-making process in the Constitution which is an indicator of the procedural review. Therefore, this study tries to answer the nature or urgency of the procedural review, by questioning what was tested by the Constitutional Court in the formal examination? This is doctrinal research which using a conceptual and cases approach in Indonesia, Kolombia, and South Africa. The selection of the case are carried out according to the functional comparative law method, which also considered on non-legal factors such as social and political factors that influence the norm. The results of the study found that the urgency of procedural review is to ensure that the law has fulfilled the aspects of legitimacy and validity. Legitimacy is arisen through meaningful participation, whereas validity comes from the conformity of the law-making processes with the procedures and can be proven materially, not only fulfilling formal requirements.